2019
DOI: 10.1016/j.jand.2018.12.011
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Digital Behavioral Weight Loss Intervention on Adherence to the Dietary Approaches to Stop Hypertension (DASH) Dietary Pattern in Medically Vulnerable Primary Care Patients: Results from a Randomized Controlled Trial

Abstract: Author Contributions Dr. Steinberg (DS) had full access to all of the data in the study and takes responsibility for the integrity of the data and the accuracy of the data analysis. DS drafted the manuscript for publication. GB conceived of the study, acquired study funding, led study design and supervised its coordination. DS coordinated intervention design. LS participated in study conceptualization and design. MK conducted statistical analysis. MK, JB and LS contributed to the drafting of the manuscript. No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 39 publications
(57 reference statements)
2
12
1
4
Order By: Relevance
“…A study showed that more than 30% of hypertension cases were caused by excessive salt intake ( 38 ); thus, BP decreased with sodium intake decreased ( 33 ). However, contradictory to other studies ( 31 ), we found a lower sodium supplication could not lead to better BP reduction. This might because the modified DASH diet was strict sodium restriction, which was generally as low as 3,000 mg. That also suggested that too low sodium intake did not reduce BP further but might reduce adherence to dietary treatment.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…A study showed that more than 30% of hypertension cases were caused by excessive salt intake ( 38 ); thus, BP decreased with sodium intake decreased ( 33 ). However, contradictory to other studies ( 31 ), we found a lower sodium supplication could not lead to better BP reduction. This might because the modified DASH diet was strict sodium restriction, which was generally as low as 3,000 mg. That also suggested that too low sodium intake did not reduce BP further but might reduce adherence to dietary treatment.…”
Section: Discussioncontrasting
confidence: 99%
“…The modified DASH diet might have greater positive or negative effects in combination with antihypertensive treatment or have higher accordance or provision of different interventions, such as dietary advice or food supplements, however, we did not have sufficient data for these analysis. Like previous studies (31)(32)(33), we found that the modified DASH diet was significantly associated with reductions in SBP, DBP, and cardiovascular risk factors. However, some discrepancies in the degree of BP and cardiovascular risk factor reduction were found.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Nonetheless, Pickering et al suggested that the potential health effects of the DASH diet are dependent on eating pattern adherence, with subjects with lower adherence to the DASH diet showing greater benefit from DASH dietary interventions in BP control than those with higher adherence before the dietary intervention [ 85 ]. Nonetheless, the commitment and implication of the patient are critical in all life-style interventions based on dietary modifications [ 86 , 87 ].…”
Section: Dash Dietmentioning
confidence: 99%